Alternating Current Potential Drop Technique to Detect Pit-to-Crack Transition. Issue 17 (2016) - Huang, Xuejun; Yu, Lun; Ballinger, Ronald
ABSTRACT: Pitting and localized corrosion can occur under various conditions and accelerate the subsequent cracking and the failure of a component. Pit-to-crack transition is considered a critical transition process and has a significant impact on the total lifetime of a component. In this study, an alternating current potential drop (ACPD) system is built and applied the detection of the pit-to-crack transition. The results show that the ACPD system is capable and sensitive to crack initiation and that the sensitivity increased with increased frequency. Crack initiation sites from pits are characterized and discussed.